The Literature Review of Cloud-based Enterprise Resource Planning. (August 2019) - Aulia, R; Putri, A N; Raihan, M F; Ayub, M; Sulistio, J
Abstract: Enterprise Resource Planning also called ERP is a system that is integrated into business processes in a company, some of the benefits of implementing ERP are higher productivity, better insights, accelerated reporting, lower risk, simpler IT and improved agility. However, ERP also has several disadvantages such as high costs, maintenance costs and this became a common problem when using the ERP system. One way to cut high costs is to use cloud computing. Cloud computing is pools of configurable computer system resources and higher-level services that can be rapidly provisioned management effort, often over the internet, cloud computing also can be the solution for companies that want to implement ERP system with low prices. In this paper, we collect several journals about cloud computing and ERP system and combine that into one literature, and this paper discusses methodology, metadata analysis and future journals related to cloud computing and ERP system